Collection, freezing of Ban epididymal sperm and evaluation of in vitro fertility after thawing - Viet Linh, Nguyen; Thi Nhung, Nguyen (Vietnam Journal of Biotechnology, 2021)
Many researches on characteristics of porcine ejaculated semen on popular commercialized breeds collecting at breeding centers or households with pig breeding services have been carried out in Vietnam. However, very few investigation had been dealt with epididymal sperms, especially the ones from boar of Ban, a popular Vietnam native mini-pig breed which is usually freely raised in far rural and mountainous regions in some provinces of Northern Vietnam. In the present study, we surveyed on criteria of epididymal sperms from 4 Ban boars at collection, after freezing and thawing processes, and tested their fertility by an in vitro fertilization and embryo culture experiment. Approximate volume of sperm collected from a Ban boar did not differ (3-4 mL), with sperm concentration from 6.4 x 109 to 11.3 x 109 sperm/mL. Motility varied from 8.7 to 27.0%, whereas vitality was from 58.0 to 85.6%. After freezing and thawing, the motility of sperm slightly decreased to values of 6.3 to 25.7%, and viability significantly decreased to values of 41.3 to 79.6%. No difference was found between rates of abnormal morphology before and after freezing and thawing (10.6 to 31.0% and 12.0 to 32.0%, respectively). A test by in vitro fertilization with Landrace oocytes revealed that two sperm lots had acceptable in vitro fertility with rates of blastocyst formation from 14.4 to 18.8%. In conclusion, a study on collection, freezing and fertility testing of epididymal sperm collected from Ban boars has been carried out. The results of the present study could contribute necessary information as well as standardized sperm lots as important materials to further research on in vitro fertilization of Ban in Vietnam.